In Vivo Detection of Postictal Perturbations of Cerebral Metabolism by Use of Proton MR Spectroscopy: Preliminary Results in a Canine Model of Prolonged Generalized Seizures - Neppl, Ronald; Nguyen, Canh M.; Bowen, William; Al-Saadi, Taoufik; Pallagi, Jeanne; Morris, George; Mueller, Wade; Johnson, Roger; Prost, Robert; Rand, Scott D. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Biochemical studies of seizures in patients and laboratory animals have monitored postictal perturbations in cerebral metabolism with either invasive techniques or with such noninvasive techniques as nuclear medicine, MR imaging, in vivo phosphorus MR spectroscopy (MRS), and in vivo proton MRS at field strengths of 1.5 T or above. We investigated postictal metabolic changes in a generalized seizure model with in vivo proton MRS at 0.5 T, in which the combination of glutamate and glutamine resonances (denoted glx) can be modeled as a singlet.METHODS: Five adult mongrel dogs underwent control and postictal experiments in which single-voxel proton MR spectra were obtained from the right frontal lobe cortex with a point-resolved spectroscopy technique approximately every 20 minutes for 3 hours. N-acetylaspartate (NAA), glx, and creatine (Cr) were quantified in absolute millimolar units with a cerebral water-referenced algorithm. Inter- and intrasubject differences in mean metabolite concentrations collected throughout the 3-hour period were compared using an unpaired, two-tailed Student's t test at a .05 level of significance.RESULTS: We found a significant increase (15.4%) in the postictal intersubject mean glx concentration, as well as a 23.7% postictal decrease in the intersubject mean Cr concentration. A trend toward a subtle decrease in postictal intersubject mean NAA concentration was not statistically significant. We also observed a substantial qualitative increase in the combination of postictal lactate and free fatty acid peaks.CONCLUSIONS: The glx, NAA, lactate, and free fatty acid results are in general agreement with previous studies of postictal perturbations in cerebral metabolism measured with invasive biochemical or noninvasive high-field-strength in vivo MRS detection assays. Given a high sensitivity for glx at 0.5 T relative to 1.5 T, further studies of postictal mesial temporal lobe structures are warranted in chronic animal preparations that model temporal lobe epilepsy.